Ultrasensitive quantification of serum vitamin D metabolites using selective solid-phase extraction coupled to microflow liquid chromatography and isotope-dilution mass spectrometry - Duan, Xiaotao; Weinstock-Guttman, Bianca; Wang, Hao; Bang, Eunjin; Li, Jun; Ramanathan, Murali; Qu, Jun (Analytical chemistry (Washington), 2010)
The capacity for quantification of active metabolites of vitamin D (VitD) is highly valuable to evaluate the risks and therapies for numerous diseases such as multiple sclerosis. However, the extremely low circulating levels and poor detectability of some dihydroxyl metabolites such as the 1alpha,25-dihydroxy-VitD(3) constitute a daunting challenge. Based on the combination of a selective solid-phase extraction (SPE) and a microflow liquid chromatography tandem mass spectrometry (microLC-MS/MS), we developed an ultrasensitive method for the robust, selective, and accurate quantification of four key VitD metabolites, including 25-hydroxy-VitD(2), 25-hydroxy-VitD(3), 24(R),25-dihydroxy-VitD(3), and 1alpha,25-dihydroxy-VitD(3), in serum samples. A one-step derivatization was employed to improve the ionization efficiency of the metabolites. The SPE procedure was optimized so that the analytes were selectively extracted from serum, while the sample matrix was substantially simplified. By eliminating majority of undesirable compounds from the matrix, the selective SPE enabled a high sample loading volume on the microLC column without causing overcapacity of the microLC column and thus helped to achieve ultralow detect limits in serum. An on-column sample focusing approach was employed to prevent band-broadening, and a sufficient microLC separation was achieved to eliminate endogenous interferences and to minimize ion suppression effect. Detect limits of the four metabolites ranged from 0.5-1 pg/mL, and the linearity was excellent for all compounds. The method showed high quantitative accuracy (error < 13.8%) and precision (CV < 14.1%). For 1alpha,25-dihydroxy-VitD(3), a lower limit of quantification (LLOQ) of 5 pg/mL was validated. This high level of sensitivity, for the first time, enabled the robust and consistent LC/MS/MS-based analysis of the four metabolites in a large-scale clinical investigation. Serum samples from 281 multiple sclerosis patients and 22 healthy subjects were analyzed, and it was discovered that the levels of both 24(R),25-dihydroxy-VitD(3) and 1alpha,25-dihydroxy-VitD(3) were significantly lower in patients than healthy subjects (P < 0.05). This novel observation may imply that the incidence of multiple sclerosis is inversely associated with the levels of the two metabolites. Moreover, the method was highly robust and reproducible as evaluated extensively in the clinical analysis; therefore, it could serve as a more selective and accurate alternative to immunoassay for large-scale clinical studies.